Trading on the arbuscular mycorrhiza market: from arbuscules to common mycorrhizal networks - Wipf, Daniel; Krajinski, Franziska; van Tuinen, Diederik; Recorbet, Ghislaine; Courty, Pierre-Emmanuel (The New phytologist, 2019)
Arbuscular mycorrhiza (AM) symbiosis occurs between obligate biotrophic fungi of the phylum Glomeromycota and most land plants. The exchange of nutrients between host plants and AM fungi (AMF) is presumed to be the main benefit for the two symbiotic partners. In this review article, we outline the current concepts of nutrient exchanges within this symbiosis (mechanisms and regulation). First, we focus on phosphorus and nitrogen transfer from the fungal partner to the host plant, and on the reciprocal transfer of carbon compounds, with a highlight on a possible interplay between nitrogen and phosphorus nutrition during AM symbiosis. We further discuss potential mechanisms of regulation of these nutrient exchanges linked to membrane dynamics. The review finally addresses the common mycorrhizal networks formed AMF, which interconnect plants from similar and/or different species. Finally the best way to integrate this knowledge and the ensuing potential benefits of AM into sustainable agriculture is discussed.